The philosophy of medicine reborn : a Pellegrino reader - Pellegrino, Edmund D., 1920-2013 (Notre Dame studies in medical ethics., 2011)
"In this anthology, H. Tristram Engelhardt, Jr., and Fabrice Jotterand have created a rich presentation of Pellegrino's thought and its development. Arguing that bioethics should not be restricted to topics such as abortion, third-party-assisted reproduction, physician-assisted suicide, or cloning, Pellegrino has instead stressed that such issues are shaped by foundational views regarding the nature of the physician-patient relationship and the goals of medicine, which are the proper focus of the philosophy of medicine."--Jacket